The impact of credit constraints on agricultural productivity in Tanzania - Msulwa, Baraka (GSB: Faculty, 2016)
This paper uses a nationally representative sample of agricultural businesses in Tanzania to empirically investigate the determinants of credit constraint status and its impact on agricultural productivity. In particular, we directly elicit the nature of the credit constraints experienced by crop producers. Subsequently, we evaluate the effect on crop output value per hectare using an endogenous switching regression model, which simultaneously estimates the likelihood of being credit constrained and its impact on productivity. The results provide evidence that the relaxation of all credit constraints would significantly enhance agricultural productivity; hence, contributing favourably to rural development, poverty alleviation, and the improvement of living standards in Tanzania. Moreover, consideration of only quantity constraints was shown to underestimate the full impact of credit constraint status in the presence of transaction costs and risk constraints. We advocate for the Tanzanian agricultural policy framework to adopt a broader definition of credit constraint status in pursuit of agricultural and economic development.